THE EFFECT OF THE REALISTIC MATHEMATICS EDUCATION (RME) LEARNING MODEL ON THE MATHEMATICS LEARNING OUTCOMES OF CLASS V UPTD STUDENTS AT SD NEGERI 235 WATALLIPUE, WAJO REGENCY - Pasinggi, Yonathan S; Shasliani, Shasliani; Sherli, Sherli (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research examines the influence of Learning Models Realistic Mathematics Education (RME) on the Mathematics Learning Outcomes of Class V UPTD Students at SD Negeri 235 Watallipue Wajo Regency, which aims to determine the description of students' mathematics learning outcomes and the influence of the application of the Realistic Mathematics Education (RME) learning model on the Mathematics Learning Results of Class V UPTD Students SD Negeri 235 Watallipue Wajo Regency. This research uses a type of pre-experimental design experimental research in the form of one group pretest-posttest. The variables in this research consist of independent variables (X) in the Realistic Mathematics Education (RME) learning model and the dependent variable (Y) is student mathematics learning outcomes. The sample for this research consisted of 21 Class V UPTD students at SD Negeri 235 Watallipue, Wajo Regency. Sampling in this research used a saturated sampling technique. The data collection techniques used are documentation and multiple-choice tests. The data analysis used is descriptive statistics and inferential statistics. The results of descriptive statistical analysis were obtained from students' pretest and posttest results with data in the form of distribution tables. The results of inferential statistical analysis consisting of normality tests and hypothesis tests using the paired sample T-test show that the average student learning outcomes in the pretest were 50.52, while the average student learning outcomes in the posttest were 82.52. Therefore, it can be concluded that the application of the Realistic Mathematics Education (RME) learning model influences the mathematics learning outcomes of class V UPTD students at SD Negeri 235 Watallipue, Wajo Regency.